Whole body positron emission tomography/computed tomography (PET/CT) tumour staging with integrated PET/CT colonography: technical feasibility and first experiences in patients with colorectal cancer. Issue 1 (10th June 2005) - Veit, P; Kühle, C; Beyer, T; Kuehl, H; Herborn, C U; Börsch, G; Stergar, H; Barkhausen, J; Bockisch, A; Antoch, G
Abstract : Aim: The aim of this study was to implement an imaging protocol for positron emission tomography/computed tomography (PET/CT) colonography and to combine this protocol with whole body PET/CT tumour staging for a single whole body examination for routine clinical use. Subjects and methods: A whole body PET/CT protocol for tumour staging and a protocol for PET/CT colonography were integrated into one examination. Fourteen prospective patients with suspected colorectal cancer underwent whole body PET/CT after aqueous bowel distension and pharmacological bowel relaxation. Colonoscopy and histopathology served as the standards of reference in all patients. Results: The modified PET/CT examination detected all but one lesion in the colon. One additional lesion was detected in a patient with incomplete colonoscopy due to high grade luminal stenosis. One polyp with malignant conversion was identified with the modified PET/CT protocol. PET/CT colonography proved accurate in local lymph node staging and staged nine out of 11 patients correctly. Six additional extracolonic tumour sites were detected based on the whole body staging approach. Conclusion: Whole body PET/CT with integrated colonography is technically feasible for whole body staging in patients with colorectal cancer. Based on these initial diagnostic experiences, this integrated protocol may be of substantial benefit in staging patients with colorectal cancer, focusing on patients with incomplete colonoscopy and those with small synchronous bowel lesions.